Phonological Process of Word-Final Consonant Sounds in Indonesian Learners by Japanese Speakers (Case Study of Japanesia Online Course Students) - mariah anggreni; Subiyanto, Agus (Universitas Negeri Semarang, 2024)
This study aims to analyze the phonological processes and contributing factors affecting the pronunciation of final consonant sounds by native Japanese speakers learning Indonesian. The research employs the theory of generative transformational phonology, using distinctive features to address the research questions. A qualitative descriptive approach was adopted, utilizing data from the Japanesia course's online class videos on YouTube, collected through observation and note-taking techniques. The analysis identifies three main phonological processes in Japanese learners' pronunciation of Indonesian final consonants: sound substitution (e.g., [n] to [ŋ] and [l] to [r]), elision of [h], and addition of sounds such as [u] following [r] and [s], as well as aspirated [h] after [t] and [k]. These phonological adjustments reflect the absence of certain Indonesian sounds in Japanese, prompting learners to adapt pronunciations to their native phonological system. Furthermore, the Japanese language’s predominant open syllable structure (CVCV) generally excludes word-final consonants aside from nasals, contributing to these adaptations.